Rat Island St. Lucia. B W I. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
This image is an aerial view of Rat Island situated in Choc Bay in St. Lucia. The buildings on this island were historically used as isolation and quarantine facilities. There are a few buildings and trees in the foreground near the water's edge. This is a divided back postcard Back of the Postcard: On the back of the postcard is marked: [55] £5.00 (Handwritten in pencil) Printed in Saxony. Peter & Co., Castries, St. Lucia
Landscape; Black & white; 3 ½” x 5 ½”
Keywords: Aerial views; Buildings; Historic buildings; Historic sites; Sanatoriums; Health care; Architectural elements